Pesantren Value Added Sebagai Modal Pemberdayaan Ekonomi Masyarakat Kecamatan Cibadak Lebak Banten - Muhammad Anwar Fathoni Fathoni; Ade Nur Rohim Rohim (Islamic Economics Journal, 2019)
This study aims to describe and analyze community economic empowerment models through added value owned by pesantren (pesantren value added). So that it can measure the extent to which pesantren resources are able to empower the economy of the surrounding community. This research is conducted at the modern boarding school Manahijussadat in Lebak Regency, Banten. This research was conducted by identifying and analyzing community economic empowerment models conducted by pesantren. This research is a descriptive study that uses a qualitative approach. The object of this research is modern boarding school Manahijussadat in Pasar Keong Village, Cibadak Lebak District, Banten. The purposive sampling technique is used in this project with both primary data and secondary data. Primary data is collected through interviews with several parties at the pesantren, while secondary data was obtained from several literatures such as books, journals and other written data. Data collection techniques used are interviews with several parties, from both top leader and management level at the pesantren as well as representatives from surrounding community. In addition, observations were also made by direct observation in the field. While the data analysis technique used in this study is qualitative analysis. Based on the research results obtained, it is known that community economic empowerment through pesantren can be built with a partnership model between pesantren, community, government and the private sector. Because pesantren is the closest Islamic educational institution to the community and has potential resources to be the pioneers of the economic empowerment of the people. The partnership can be carried out in several aspects such as employment, business opportunities, and the establishment of business entities or financial institutions. The partnership that exists between these four elements can make people more economically empowered and improve their welfare in a sustainable manner.